New literacies practices of teenage Twitter users. Issue 1 (2nd January 2016) - Gleason, Benjamin
Abstract : This study is an empirical study into the new literacy practices of five teenage Twitter users on Twitter. Qualitative methods were used to describe the most prominent ways of participating on Twitter . Results indicate that teenagers used Twitter for self-expression, communication, friendship maintenance, and information sharing. In addition, young people used a mix of both traditional and emerging literacy practices in this popular social media space.